1973
DOI: 10.1002/1097-4679(197304)29:2<225::aid-jclp2270290220>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

The factor structure of the 16 PF and the edwards personal preference schedule in acute psychiatric patients

Abstract: A circumplex model for maternal behavior. J . abn. soc. Psychol., 1959, 69, characteristics: an interdimensional analysis. Psychol. Rep., 1958, 4, 279-319. Psychol., 1954, 7 , 477-484. Rev., 1961, 68, 341-353. ideal percepts in college women. J. SOC. Psychol., 1963, 61, 335-344. related to college achievement. J. SOC. Psychol., 1967, 73, 253-259. understanding family dynamics: case report. J. clin. Pschol., 1961, 17, 225-228. measured by the Edwards PPS and interpersonal check list.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…The primary objective of the present study was to examine the factor structure of the Edwards Personal Preference Schedule (EPPS; Edwards, 1959) for males and females separately. Although a number of factor analytic studies and studies that examined sex differences have been reported on the EPPS (Beckner, 1974; Dixon & Ahern, 1973; Edwards, Abbott, & Klockais, 1972; Kear-Colwell, 1973;Murgatroyd & Gavurin, 1975;Scott & Manaugh, 1976;Sherman & Poe, 1972), there is little information on sex differences in factor structure.…”
mentioning
confidence: 99%
“…The primary objective of the present study was to examine the factor structure of the Edwards Personal Preference Schedule (EPPS; Edwards, 1959) for males and females separately. Although a number of factor analytic studies and studies that examined sex differences have been reported on the EPPS (Beckner, 1974; Dixon & Ahern, 1973; Edwards, Abbott, & Klockais, 1972; Kear-Colwell, 1973;Murgatroyd & Gavurin, 1975;Scott & Manaugh, 1976;Sherman & Poe, 1972), there is little information on sex differences in factor structure.…”
mentioning
confidence: 99%